URGENSI PERUBAHAN KARIR PNS MENUJU PENYELENGGARAAN TATA KEPEMERINTAHAN YANG BAIK - Iswahyudi, Fajar (Jurnal Borneo Administrator, 2008)
From the three of the characteristics of career path (defined from three stages career changes from  traditional career path to transition career path and to  protean career path), Civil Servant career in Indonesia is still have the traditional path; this justification which taken from the characteristics of the Civil servant career at the moment. This condition is describing that the Indonesia Civil Servant career is left behind compare with the other country. This condition also indicate that the cause of the problem on employment in Indonesia. So, the Indonesia Civil servant career has to evaluate to achieve the effective and efficient Human resources.  Keywords:  Traditional Career, Protean Career, Care Path